A Lawyer’s Divorce: Will Decentralized Ledgers and Smart Contracts Succeed In Cutting Out the Middleman? - Charlotte R. Young (Washington University Law Review, 2018)
Society is progressing at a rapid pace. As math and science evolve, new technologies begin to utilize these advances and create something novel. These technological changes are revolutionizing not only the science-oriented industries, but also the humanities. One such example falls within the legal arena. More specifically, the exciting advent of smart contracts and their use of technological changes are altering the way law is processed and practiced. However, as is often the case, new technological innovations spur certain growing pains. The implementation of smart contracts is proving no different. Some view the smart contract as the start of a more ideal society. With the aid of smart contracts and blockchain technology, machines can finally be equipped to fulfill some of the most basic human functions. Not only would business transactions always occur in a timely, seamless, and cost-effective manner, but also more mundane life tasks, such as ordering laundry detergent, could soon be done via smart contract technology. As exciting as these changes may be, smart contracts and the blockchain technology behind them are still immature. Before this legal phenomenon is widely accepted, there needs to be more advancement in not only the code that creates the technology, but also in the law and its regulations. As it stands today, smart contracts are most likely to be accepted only in part, and heavily tailored to meet each contracting party’s needs. This Note will start by giving an overview of the technology needed to implement smart contracts—blockchain technology—and an explanation of how smart contracts fit within the framework of a blockchain. Next, this Note will discuss some of the major issues smart contracts face. Such issues include: the need to translate natural language into computer code, the traditional concept of contracting in conjunction with the effect of smart contracts on traditional legal notions, and reoccurring enforcement issues. After discussing smart contracts and the current issues barring wide-spread acceptance, this Note will explore the future of smart contracts in the legal arena by analogizing such an electronic contracting change to the now-widely accepted electronic clickwrap agreements. Additionally, this Note will explore recently enacted state statutes that create favorable legal conditions for smart contracts and what impact, if any, these statutes may have upon federal legislation. Furthermore, this Note will analyze the lack of and potential need for regulations regarding smart contracts. In an attempt to make smart contracts acceptable, this Note will suggest future regulations focus on two components of smart contracts. As it will be discussed, regulations should require smart contracts to utilize a permissioned ledger and focus on ensuring the legal requirement of mutuality between the two contracting parties. Lastly, this Note will conclude that although the publicity surrounding smart contracts is exciting and innovative, this form of contracting is likely to remain in a controlled business environment with implementation under select circumstances.
Keywords: Decentralized Ledgers; Smart Contracts; Middleman; blockchain technology; natural language; clickwrap agreements; permissioned ledger; mutuality; contract law; checking mechanism; ledger; decentralized; blockchain network; permissionless; computer code; Common Language for Augmented Contract Knowledge; CLACK; DAO Hack; Decentralized Autonomous Organization; Genesis DAO; acknowledge box; Arizona Electronic Transaction Act; Illinois Blockchain Initiative; Uniform Electronic Transactions Act; UETA; Electronic Signatures in Global National Commerce Act; ESIGN; Controlled Business Environment; anonymity; acceptance; DAO hack